Atividade imunomodulatória do extrato aquoso obtido da casca do caule da Bowdichia virgilioides Kunth no timo de camundongos - Vieira, Larissa Fernanda de Araújo (2011)
The plant species Bowdichia virgilioides Kunth, popularly known as "sucupira", is used by regional folk medicine as a treatment for gout, inflammation and autoimmune diseases. However, few scientific studies dealing with its biological activity, especially with regard to the immune system, making this species a potential target for scientific investigation. The aim of this study was to evaluate in vivo the action of aqueous extract of the stem bark of B. virgilioides (EABv) on the thymus. For that, male C57BL6 mice (4-5 weeks) were used and treated orally for 7 days with EABv. Initially, histological examination revealed that treatment with EABv change the morphology of the thymus, and significantly reduces organ weight and total thymocyte numbers. It was found by flow cytometry that this reduction occurred in double-positive thymocyte (CD4+CD8+) and single positive thymocyte (CD4+CD8- and CD4-CD8+). Furthermore, by indirect immunofluorescence, we observed an enhancement in laminin and fibronectin deposition in the thymus of EABv-treated animals compared with control group. However, cytometric analysis showed that EABv was not able to influence the expression of integrin receptors VLA-5 and VLA-6 on the surface of thymocytes. Moreover, thymocyte adhesion to laminin was diminished in EABv-treated animals and this reduction occurred in immature (CD4-CD8- and CD4+CD8+) cells and mature (CD4+CD8- and CD4-CD8+) cells. Lastly, thymocyte migration was measured using transwell chambers and revealed that this extract reduced thymocytes migration driven by laminin and that this decline occurred mainly in CD4+CD8+ cells. These results show that the EABv interfere in the immune system by reducing the weight of the thymus and the total thymocyte numbers, in addition to negatively modulate the adhesion and migration of these cells, suggesting its role as an immunosuppressive substance.